Religiosity and Halal Certification: Its Effect on Interest in Buying Traditional Food - Najmudin, Najmudin; Syihabudin, Syihabudin (Li Falah: Journal of Islamic Economics and Business, 2021)
This study aims to determine (1)—the influence of religiosity on the interest in buying traditional food of sate bandeng. (2). The effect of halal certification on the interest in buying traditional food of sate bandeng. And (3). The impact of religiosity and halal certification on interest in buying traditional food of sate bandeng. This research is the millennial consumers of traditional food of Sate Bandeng Kang Cepi Kaujon, Serang City, Banten Province. The research method used is quantitative. Methods of data collection using a questionnaire. Data were processed using SPSS version 23 software. Data analysis used the multiple linear regression method. The results of this study indicate that (1). Religiosity affects an interest in buying traditional food of Sate Bandeng. (2). Halal certification affects an interest in buying traditional food of sate bandeng (3). Religiosity and halal certification have a positive and significant impact on interest in buying traditional food of Sate Bandeng. Consumers’ interest in buying traditional food of Sate Bandeng is influenced by religiosity and halal certification as much as 48.8 percent. In comparison, the remaining 51.2 percent is influenced by other variables not examined in this study.